Advances in civil engineering : structural seismic resistance, monitoring and detection : proceedings of the International Conference on Structural Seismic Resistance, Monitoring and Detection (SSRMD 2022), Harbin, China, 21-23 January 2022 /: structural seismic resistance, monitoring and detection : proceedings of the International Conference on Structural Seismic Resistance, Monitoring and Detection (SSRMD 2022), Harbin, China, 21-23 January 2022. (2022) - Unknown
No abstract available